Periodismo digital como alternativa de desarrollo comunitario en la Parroquia San Camilo en el Sector Los Chapulos, año 2020 - Mendoza Pacheco, Mercy Cecibel (2021)
For readers interested in events around the world, digital news is a direct and accessible source of information. Through digital news, information can be obtained immediately when an event occurs, in addition, this type of media also provides the possibility for each listener to exchange opinions about news and contribute to related research. Unlike other media, this medium has many advantages, such as news in real time with sound and images, links to other pages and social interaction. Digital news involves the entire informational process using the resources provided by technology to promote the continuous development of the information that the audience receives at any time and place. Some people believe that print newspapers will disappear over time due to technological advances in digital newspapers with multimedia content (text, images, audio and video) and support. In Ecuador, digital media have been integrated into the new platform and even managed to increase the audience due to its immediacy. Fewer and fewer people are looking for information through newspapers, television or radio because they already have smartphones and can use these smartphones to access social media to find the latest world news. The different social networks allow us to maintain instant communication with other people, which also allows us to speak, listen and communicate directly with your community, which is a more user-friendly service. It should be noted that it is a powerful means of disseminating news, it also allows us to attract the attention of users or customers, at the same time that we can listen to the voice of the audience and communicate more directly.